Environmental evaluation of metals in sediments and dragonflies due to sugar cane cultivation in neotropical streams - Corbi, Juliano Jose; Trivinho-Strixino, Susana; Santos, Ademir dos [UNESP] (Springer, 2008)
The use of fertilizers, containing different metals ions such as lead(II), chromium(III), cadmium(II), copper(II) and zinc(II), in the soil, for sugar cane cultivation, may cause impacts on the hydric resources of the adjacent areas. The scope of this study was to evaluate the impacts of sugar cane cultivation based on metal concentrations in sediments and dragonflies (Odonata). The bioavailability of such metals was determined in ten Neotropical streams. Six streams were located on areas with sugar cane cultivation, without riparian vegetation (classified as impacted area) and four streams were located on forested areas (reference sites). The results showed that there are high concentrations of metals in the sediments and dragonflies in streams located on impacted areas. The contamination by metals of aquatic insects of terrestrial adult life cycle, as Odonata organisms, represents a dangerous link for the transference of metals to upper trophic levels, as fishes, reptiles, birds and mammals.
Keywords: metals; streams; dragonflies; sugar cane cultivation; sediments; Brazil